Hydrochemical study of the Caldas Novas Thermal Complex (GO), Brazil - Lunardi, Marina [UNESP]; Bonotto, Daniel Marcos [UNESP] (Springer Nature, 2018)
The city of Caldas Novas, State of Goiás, Brazil, holds the largest thermal water complex in the planet not associated to with volcanism or other kinds of magmatism. Its structural control allows the fractures to be wide and deep enough so the waters can reach 1000 m depth. These waters are extracted mainly by deep wells, from the exploitation of the Paranoá and Araxá Aquifer Systems, emerging at temperatures higher than 59 °C. With a growing demand for water resources, groundwater exploration became an attractive alternative for public supply, due to its abundance, quality and low abstraction cost. In Caldas Novas, due to the population growth over the last decades and the increasing number of tourists, a disordered groundwater consumption drawdown the water levels. In order to survive, these reservoirs depend on rainwater infiltration rates to replenish the thermal springs; however, the lack of environmental management and the high risk of contamination, due to the unconsolidated materials thinness, may threaten the thermal aquifer. This study was based on the hydrochemical characterization of Caldas Novas Thermal Complex waters, including radioactive parameters, whose descriptions in the literature are still scarce. Besides, concerning the prospective increase on touristic activities, physicochemical water analyses are periodically required, being this paper a contribution for such purpose.
Keywords: Caldas Novas; Hydrochemistry; Radon; Thermal aquifer; Uranium